2017
DOI: 10.1371/journal.pone.0179359
|View full text |Cite
|
Sign up to set email alerts
|

Climatic anomaly affects the immune competence of California sea lions

Abstract: The past decades have been characterized by a growing number of climatic anomalies. As these anomalies tend to occur suddenly and unexpectedly, it is often difficult to procure empirical evidence of their effects on natural populations. We analysed how the recent sea surface temperature (SST) anomaly in the northeastern Pacific Ocean affects body condition, nutritional status, and immune competence of California sea lion pups. We found that pup body condition and blood glucose levels of the pups were lower dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 48 publications
3
12
0
Order By: Relevance
“…Therefore, it is not surprising that the average blood glucose levels and growth rate of pups were highly correlated in our study, suggesting that glucose could be a good marker of the energy balance in a pup, and an important factor to consider in the health assessment of wild pinnipeds given the connection between energy balance and immune system. For instance, recent studies have shown that Californian sea lion pups with better body condition and higher glucose levels have higher total IgG ( Banuet-Martínez et al, 2017 ). In humans and laboratory animals, glucose metabolism is one of the most important factors driving T-cell activity and production of antigen-specific IgG ( Mohammed et al, 2012 ; Palmer et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is not surprising that the average blood glucose levels and growth rate of pups were highly correlated in our study, suggesting that glucose could be a good marker of the energy balance in a pup, and an important factor to consider in the health assessment of wild pinnipeds given the connection between energy balance and immune system. For instance, recent studies have shown that Californian sea lion pups with better body condition and higher glucose levels have higher total IgG ( Banuet-Martínez et al, 2017 ). In humans and laboratory animals, glucose metabolism is one of the most important factors driving T-cell activity and production of antigen-specific IgG ( Mohammed et al, 2012 ; Palmer et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, the mechanisms that drive decreased survival during years with low ocean productivity have not been intensely explored beyond assuming that this results from direct mortality because of starvation. However, in some otariid populations, in years with abnormal SST, the immune competence of pups decreases ( Banuet-Martínez et al, 2017 ), suggesting that environmental variables can affect the health of marine mammals by impairing their immune function. If these immunological changes impact offspring survival, there could be additional negative consequences between a warmer ocean, health, and survival of marine vertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…RBC and HG were measured as previously described ( Seguel et al, 2016 ), and anemia defined as HG concentrations below 10 g/dL and/or RBC bellow 3 × 10 3 /μL, according to published reference values for pups in this population ( Seguel et al, 2016 ). Additionally, we recorded the scaled body mass (total length/weight) (BM) ( Banuet-Martinez et al, 2017 ), total serum protein concentration (TP) and white blood cell counts (WBC) as general measurements of the pups' health. These indicators were measured in each capture following previously described methods ( Seguel et al, 2016 ), and the average for each pup was used for statistical analyses.…”
Section: Methodsmentioning
confidence: 99%
“…When forced to increase foraging effort, nursing adult female sea lions have difficulty in allocating resources towards pup development (Ono et al , 1987). Additionally, body condition and glucose-dependent immune markers, IgG and IgA (Palmer et al , 2015), were reduced in dependent CSL pups born during anomalous conditions of high SST in 2015 (Banuet-Martínez et al , 2017), and also showed abnormalities to erythrocytes, which can further impact nutrient uptake (Flores-Morán et al , 2017). This extended period presented a unique opportunity to investigate the effects of sustained stressors on CSL facing abnormally high energetic demands.…”
Section: Introductionmentioning
confidence: 99%